Why do People's complaints still fall on the police? Confidence in the police in Trinidad and Tobago - Baek, Hyunin (International journal of law, crime and justice, 2020)
Law enforcement agencies in Caribbean countries, especially Trinidad and Tobago, have been struggling with low levels of public confidence. To examine the public-police relationship in these countries, this study proposed and tested two models of public confidence in the police using data from a sample of 1,595 adults in Trinidad and Tobago. Findings from Structural Equation Modeling indicated that public confidence in the police was driven not only by actual crime and fear of crime but also by other variables such as community cohesion, social problems, and informal social control. The findings provide valuable insights which help to clarify the nature of the public-police relationship in Trinidad and Tobago and suggest that attention to a wider range of variables can be used to build public confidence in the police.